2017
DOI: 10.1515/pjvs-2017-0076
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of body surface area-based and weight-based dosing format for oral prednisolone administration in small and large-breed dogs

Abstract: This study compared the pharmacokinetics of Prednisolone (PDS) in small-and large breed dogs with a dosing format based on body surface area (BSA) or body weight (BW). The maximum concentration and area under the curve in large-breed dogs orally administered 2 mg/kg PDS were significantly greater than those in small-breed dogs given 2 mg/kg and in large-breed dogs given 40 mg/m 2 . The higher blood concentrations that result from BW-based dosing of oral PDS in large-breed dogs can be more than required for eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Many BCCs and practitioners in PCPs made allowance for bodyweight when selecting doses of prednisolone for initial treatment of dogs with IMHA. This is important because metabolic rate is more closely related to surface area than bodyweight [ 28 ], meaning that lower total doses are required to achieve the same blood concentrations of prednisolone in larger dogs [ 29 ]. Consequently, dosing according to surface area may be an effective practice to limit adverse effects in larger dogs, as recommended previously [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many BCCs and practitioners in PCPs made allowance for bodyweight when selecting doses of prednisolone for initial treatment of dogs with IMHA. This is important because metabolic rate is more closely related to surface area than bodyweight [ 28 ], meaning that lower total doses are required to achieve the same blood concentrations of prednisolone in larger dogs [ 29 ]. Consequently, dosing according to surface area may be an effective practice to limit adverse effects in larger dogs, as recommended previously [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation may be the signalment of dogs with SRMA that are substantially larger (median bodyweight of 29 kg in the present study) compared with dogs with MUO (typically small breed dogs). In large breed dogs different pharmacokinetics of steroids may result in more clinically relevant side effects 37 . Possibly using the body surface as a basis for the calculation of the prednisolone dosage instead of the bodyweight, some of the side effects could be reduced as suggested in a recent publication 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In large breed dogs different pharmacokinetics of steroids may result in more clinically relevant side effects 37 . Possibly using the body surface as a basis for the calculation of the prednisolone dosage instead of the bodyweight, some of the side effects could be reduced as suggested in a recent publication 37 . A third reason might be different reporting schemes: while in the present study all clinical and laboratory abnormalities were reported during treatment, previous studies mainly included adverse events clearly related to the administration of CA.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the enzyme's activity is limited in cats, which explains why oral prednisolone is preferred over prednisone in this species (7). In fact, prednisolone is frequently selected over its prodrug in dogs as no further hepatic biotransformation is required (19,20), and the PK data available in the scientific literature is more robust for prednisolone than prednisone (10,(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%